(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
This issue investigates the current state and possible developments of Media Industry Studies in Italy. Through multiple perspectives and research methodologies, it offers insights on the changing role of Italian public service broadcasting, on the network relations and modes of production of Italian cinema in the 1950s and 1960s, and on the challenges posed by the contemporary media landscape.